Stereotactic Radiosurgery Hypophysectomy for Palliative Treatment of Refractory Cancer Pain: A Historical Review and Update - Larkin, M. Benjamin; Karas, Patrick J.; McGinnis, John P.; McCutcheon, Ian E.; Viswanathan, Ashwin (Frontiers in Oncology, 2020)
Medically refractory pain in those with advanced cancer significantly reduces one's quality of life. Therefore, palliative interventions to mitigate cancer pain and reduce opioid requirements are necessary to reduce patient suffering and opioid-induced side effects. Hypophysectomy, a largely forgotten pain procedure with several technical variations, has been repeatedly studied in small series with encouraging results, though historically has been fraught with complications. As a result, the minimally invasive and more tolerable stereotactic radiosurgery (SRS) hypophysectomy has resurfaced as a possible treatment for cancer-related pain. While the mechanism of pain relief is not entirely understood, the hypothalamohypophyseal axis appears to play an essential role in pain perception and transmission and involves C fiber signal processing and downstream modulation of the brainstem and spinal cord via the hypothalamus. This review highlights the role of hypophysectomy in alleviating advanced cancer pain, both in hormonal and nonhormonal malignancy and the current mechanistic understanding of pain relief for the three primary hypophysectomy modalities used historically: surgical and chemical adenolysis, as well as the more recent, SRS hypophysectomy. Given the lack of high-quality evidence for stereotactic radiosurgery hypophysectomy, there is a need for further rigorous and prospective clinical studies despite its ideal and noninvasive approach.